Generation of business process modeling notation diagrams from textual functional requirements in Indonesian - Sholiq, Sholiq; Yaqin, Muhammad Ainul; Subriadi, Apol Pribadi; Setiawan, Bambang (International Journal of Electrical and Computer Engineering (IJECE), 2025)
This study proposes a method for converting textual functional requirements in Indonesian to business process modeling notation (BPMN) diagrams. has not been found in previous studies. The use of BPMN diagrams to present software functional requirements has the advantage of being better in terms of presenting sequential activities than using use case diagrams. On the other hand, the requirements obtained from clients in the requirements collection session are more in the form of user stories, namely text in natural language. The method used in this study is to integrate natural language processing and a set of mapping rules and BPMN diagram generation rules. The proposed method is tested with 15 functional requirement cases from three applications, namely mini hospital software, employee cooperatives, and stores. Then, the results are compared with diagrams made by experts for the same cases. The test results show an accurate level of the proposed method of 94.4%.